2010
DOI: 10.1073/pnas.1004569107
|View full text |Cite
|
Sign up to set email alerts
|

Multidomain assembled states of Hck tyrosine kinase in solution

Abstract: An approach combining small-angle X-ray solution scattering (SAXS) data with coarse-grained (CG) simulations is developed to characterize the assembly states of Hck, a member of the Srcfamily kinases, under various conditions in solution. First, a basis set comprising a small number of assembly states is generated from extensive CG simulations. Second, a theoretical SAXS profile for each state in the basis set is computed by using the Fast-SAXS method. Finally, the relative population of the different assembly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
200
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 195 publications
(202 citation statements)
references
References 33 publications
2
200
0
Order By: Relevance
“…Activation of the enzyme is induced by Tyr dephosphorylation and other modifications, which release intramolecular contacts and lead to a largely disassembled and more disordered active state. Recent SAXS experiments 26 showed an ensemble of distinct closed and open structures in both the inactive and active states ( Figure 2D), therefore signaling due to dephosphorylation is best described as a shift in the conformational ensemble. 26 In a way similar to the case of interdomain allostery, Hck also represents a combination of traditional and novel types of allostery, because shifts in the population are converted to structure-based signal propagation in the catalytic domain (Table 2).…”
Section: Autoinhibitionmentioning
confidence: 99%
See 3 more Smart Citations
“…Activation of the enzyme is induced by Tyr dephosphorylation and other modifications, which release intramolecular contacts and lead to a largely disassembled and more disordered active state. Recent SAXS experiments 26 showed an ensemble of distinct closed and open structures in both the inactive and active states ( Figure 2D), therefore signaling due to dephosphorylation is best described as a shift in the conformational ensemble. 26 In a way similar to the case of interdomain allostery, Hck also represents a combination of traditional and novel types of allostery, because shifts in the population are converted to structure-based signal propagation in the catalytic domain (Table 2).…”
Section: Autoinhibitionmentioning
confidence: 99%
“…24 It also became clear that allosteric coupling might occur without a discernible conformational change, by way of altering the dynamics of the protein only 6,21,25 ( Figure 1C) to favor a particular downstream binding/catalytic event. By combining elements of classical cooperativity (subunit interactions) and conformational coupling augmented by structural disorder (novel allostery), recently it was also reported that domaindomain interactions enabled by a disordered linker 13,26 might permit the formation of an energetic pathway traversing separate domains through their interface (Figure1D).…”
Section: Structural and Dynamic Basis Of Allosterymentioning
confidence: 99%
See 2 more Smart Citations
“…These developments have generated an interest in developing new methods to make optimal use of the available experimental data. From the initial emphasis on the determination of the native structures of proteins, the focus is increasingly shifting toward generating conformational ensembles representing their conformational fluctuations (2)(3)(4). In this context, problems with overfitting are systematically addressed (5), and in general efforts are made to implement the structural restraints as conservatively as possible, for instance by using the maximum entropy principle (6)(7)(8)(9).…”
mentioning
confidence: 99%